Kewaspadaan Terhadap Kanker pada Perempuan Keturunan Pasien Kanker Payudara - Boby Febri Krisdianto; Fitri Mailani (NERS Jurnal Keperawatan)
Genetic factors play an essential role in causing breast cancer, especially in children who have mothers with breast cancer. Such children possess a two times greater chance of suffering breast cancer. Rarely did studies use qualitative methods to explore the experience of children from mothers diagnosed with cancer in cancer awareness and prevention. Therefore, this research used qualitative research by means of a phenomenological approach. Interviews were conducted for 15 days by means of a purposive sampling data collection technique. Data were taken from in-depth interviews with women at risk of breast cancer, whose mothers were diagnosed with breast cancer. At the end of data collection, data saturation occurred for the 10th participant. After the data was analyzed using the Collaizi technique, it was extracted, then it was classified into 3 themes as follows: 1) Lack of knowledge in recognizing signs and symptoms of breast cancer, 2) The positive role of husband's support, 3) Anxiety in early detection of breast cancer. This research emphasizes the importance of a woman who is at risk of breast cancer from her mother getting counselling and health education about cancer awareness by reflecting on her mother diagnosed with breast cancer. It is proved that educating the husband probably affects the prevention of breast cancer.